Respostas

2014-05-27T22:04:47-03:00
3(x²-1)=2x(x+1)
3*x²-3*1=2x*x+2x*1
3x²-3=2x²+2x
3x²-3-2x²-2x=0
x²-2x-3=0

(-2)²-4*1*(-3)
4+12=16

(2+ \sqrt{16} ) / 2 =3
(2-  \sqrt{16} ) /2 = -1

Então x=1 ou x=3
2014-05-27T22:33:24-03:00
3(x² - 1) = 2x(x +1)
3 . x
² - 3 . 1 = 2x . x + 2x . 1
3x² - 3 = 2x² + 2x
3x² - 3 - 2x² - 2x = 0
x² - 2x - 3 = 0 (a = 1, b = -2 e c = -3)
 Δ = b² - 4ac
 Δ = (-2)² - 4 . 1 . (-3)
 Δ = 4 + 12
 Δ = 16
   x = - b ± √Δ / 2a
   x = - (-2) ± √16 / 2 . 1
   x' = 2 + 4 / 2 = 6 / 2 = 3
   x'' = 2 - 4 / 2 = -2 / 2 = -1
As raízes da equação são -1 e 3.

Espero ter ajudado. Valeu!
     
1 4 1